If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -21 = -11 Reorder the terms: -21 + x = -11 Solving -21 + x = -11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + x = -11 + 21 Combine like terms: -21 + 21 = 0 0 + x = -11 + 21 x = -11 + 21 Combine like terms: -11 + 21 = 10 x = 10 Simplifying x = 10
| k+42=14k | | X-7=4x-2 | | 3x+5(x-2)=6(x+4) | | 4-6x=7-2x | | 120+20x=60x | | 152=x-49 | | 23=-3x-2(-6x+11) | | 4/56/x | | m-1/6-4m-5/6= | | 4/56x | | 27/945/15 | | 4c-6x+2=0 | | x+x-4-2x=24 | | 37=x-49 | | (2x+1)=(6x-1) | | m--1/6-4m-5/6 | | x^2+17x+72=3 | | x=6.35+9.15 | | 8+x+3x=48 | | 27/94515 | | 13-2/9g=-8 | | 9/x=1/18 | | 3p-20=4+5p | | -4+q=11 | | rsx-t=9 | | (9-x)(7-x)=35 | | 45=25y | | 9x=1/18 | | -2x-53=-15 | | 11y-3y-7y=11 | | 15x+4-5x=10x+104 | | 1.66666(8t-5)=(t+5)(0.08333333) |